Visi dan Strategi Universitas Menghadapi Abad XXI - Khaerudin Kurniawan (Universitas Negeri Malang, 2016)
Facing 21st century, human resources play a dominant role in accelerating the national growth and development. University, as a subsystem of the national education system, has to prepare its students to be members of Indonesian society having academic capabilities and professional skills in developing science, technology, and art to improve the quality of societal life and to enrich our national culture. An optimistic vision in the scientific community should be developed continuously. the development of science, technology, and art has to be oriented to the needs of national development. University poses itself to be a scientific-dynamic community having understanding of national culture and personality, and appreciating and implementing the Five Principles (Pancasila)